Tales and stories to enhance reading skills in 10TH grades at unidad educativa Guillermo Ordóñez Gómez - Del Pezo Tomalá, Dannis Alexis (2022)
It was decided to create this project in order to enhance English reading skills to tenth-grade students at the Universidad Educativa "Guillermo Ordóñez Gómez" during the school year 20212022. The primary objective of this research was to develop an online blog based on Ecuadorian tales and stories with its activities, which would allow students to enhance their English reading skills while doing so. Several tools were used to accomplish this goal during this research. In order to gather information regarding the students' learning process, the quantitative technique was used, which included questionnaires and surveys administering to English teachers allowing to determine that the students have a limited English reading skill. All of this information was used to develop an offer that met the students' requirements, and with the assistance of reading comprehension activities, it was possible to create an online blog for the 10th grade students, keeping in mind the Ecuadorian tales and stories they heard before. As a teacher, you will find this guide to be a very useful tool in providing your students with a diversely interesting method that can include each and every one of them during the development of each lesson while practicing and improving the skills to achieve English proficiency.